BOOK REVIEW : The Appearances of Memory. Mnemonic Practices of Architecture and Urban Form in Indonesia - Cuthbert, Alexander R. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 1 No 1 (2014): April 2014, 2014)
-
Keywords: -